The media waging of a crusade a critical discourse analysis of the Philippine News Agency’s (PNA) reportage of Duterte’s “War on Drugs” - Ronquillo, Franz Andrew E.; Lambino, Marichu (Quezon City University of the Philippines, Diliman, 2025)
This thesis explored how the Philippine News Agency (PNA) presented the Duterte administration's killings during drug operations and the overarching Duterte policy of such killings. By employing Fairclough’s (1995) three dimensions of Critical Discourse Analysis, this study examined how former president Rodrigo Duterte delivered his electoral promise of solving the illegal drug situation in the Philippines through his whole-of-nation approach, mechanizing the police force to conduct a war against the state’s perceived social enemy, that is, drugs—with no reservations to human rights. This study underscored the role of state media as a loyal facilitator of government discourse to diminish the criticisms against the “drug war” through its privileging of state data, actor representations, and decontextualization of drugs as mainly a criminal element. In doing so, PNA has reinforced Duterte’s ideology to securitize illegal drugs to maintain his populist power and control. The study concluded that the news agency was complicit in bannering the discourse that the “War on Drugs” was a necessary policy to save the country from social menace, irrespective of its violence and injustice.
Thesis
Keywords: Duterte, Rodrigo Roa -- 1945-.; Drug control -- Philippines -- Press coverage; Mass media -- Political aspects -- Philippines; Press and propaganda -- Philippines